Pengaruh Tata Kelola Kehadiran terhadap Kinerja Karyawan PT Sumber Alfaria Trijaya Tbk (Branch Karawang) - Yunaika Wardani; Yudi Kristanto; Wanda Ilham (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This research is motivated by the importance of employee performance as a key factor in the success of a company. At PT Sumber Alfaria Trijaya, Tbk (Karawang Branch), a phenomenon was found in which employee attendance discipline did not align with performance and compensation. Several employees who frequently arrived late still received the same salary and incentives as those who were punctual, creating a perception of unfairness and potentially lowering work motivation. The purpose of this study is to analyze the implementation of attendance governance, evaluate employee performance, and examine the influence of attendance governance on employee performance. This study applies a quantitative approach using a survey method with questionnaires. The sample was determined using Slovin’s formula, resulting in 165 respondents from a population of 279 employees. Data analysis was conducted through validity and reliability tests, simple linear regression, t-test, F-test, correlation, and coefficient of determination with the help of SPSS software. The findings indicate that attendance governance has a positive and significant effect on employee performance. The use of an electronic attendance system, routine monitoring, and the implementation of sanctions and rewards have proven effective in improving discipline, productivity, work quality, and responsibility. The coefficient of determination also shows that attendance governance contributes significantly to performance improvement. In conclusion, fair, consistent, and technology-based attendance governance enhances motivation and performance, while fostering a more productive and harmonious work environment.